2004
DOI: 10.1002/jso.20161
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal heated chemotherapy affects healing of experimental colonic anastomosis: An animal study

Abstract: Cytoreduction and HIPC are gaining popularity. However, the use of heated chemotherapy has a detrimental effect on the strength of colonic anastomosis, especially during the early postoperative period (until day 10). This may cause anastomotic failure and postoperative morbidity. Therefore, careful selection and avoidance of unnecessary anastomoses are mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 24 publications
6
27
0
Order By: Relevance
“…However, they presented 3 times higher risk of developing a GIII–IV postoperative complication compared with those who were submitted to IPHP with a lower CDDP dose, when adjusted for the other variables. This finding, at first glance, should not be surprising as it can be supported by an experimental study, which demonstrated the negative influence of CDDP on healing of bowel anastomosis after IPHP 18. In addition, the digestive complications due to anastomotic leaks and/or bowel perforations were the most frequent type of major morbidity in the present series, as already discussed.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, they presented 3 times higher risk of developing a GIII–IV postoperative complication compared with those who were submitted to IPHP with a lower CDDP dose, when adjusted for the other variables. This finding, at first glance, should not be surprising as it can be supported by an experimental study, which demonstrated the negative influence of CDDP on healing of bowel anastomosis after IPHP 18. In addition, the digestive complications due to anastomotic leaks and/or bowel perforations were the most frequent type of major morbidity in the present series, as already discussed.…”
Section: Discussionsupporting
confidence: 87%
“…The influence of chemotherapy on the suture‐line healing depends on the type of drug. In animal studies, anastomotic healing can be impaired by intraperitoneal MMC17 and cisplatin18 but not by 5‐fluorouracil19 or paclitaxel 20. Local hyperthermia in itself has no adverse effect on anastomotic healing in animal models 21.…”
Section: Discussionmentioning
confidence: 99%
“…As many series (19), important part of our morbidity is represented by leakages. It has been proved that the use of heated chemotherapy has a detrimental effect on the strength of colonic anastomosis, especially during the early postoperative period (until day 10) (20,21). This may cause anastomotic failure and postoperative morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Both experimental and clinical studies show that HIPEC has negative effects on anastomotic healing. Surgeons may prefer either ileostomy or colostomy to prevent abdominal sepsis because of anastomosis leakage (AL), which results in the reduction of patients' quality of life, increased mortality, and morbidity …”
Section: Introductionmentioning
confidence: 99%